The Chemokine CXCL7 Is Related to Angiogenesis and Associated With Poor Prognosis in Colorectal Cancer Patients - Li, Longhai; Jiang, Kai; Li, Dongpeng; Li, Dongxiao; Fan, Zitong; Dai, Guosheng; Tu, Sheng; Liu, Xiangyu; Wei, Guangyou (Frontiers in Oncology, 2021)
Objective: The present study was designed to investigate the role of the chemokine CXCL7 in angiogenesis and explore its prognostic value in colorectal cancer (CRC). Methods: A total of 160 CRC patients who had undergone surgery were included in this study, and staged according to the guidelines of the AJCC, 7th Edition. Expression of CXCL7 and VEGF was detected by immunohistochemical (IHC) staining and divided into high and low expression subgroups. The correlation between CXCL7 and VEGF expression was evaluated by Spearman's rank-correlation coefficient. Prognosis based on CXCL7 and VEGF was evaluated using the Cox proportional hazards regression model and a nomogram of 5-year overall survival (OS) time. Results: CXCL7 was highly expressed in tumor tissues (65.63% vs 25.00% in paracancerous tissue, P < 0.001), as was VEGF. CXCL7 and VEGF expression correlated well with N and TNM stage cancers (all P < 0.001). Importantly, CXCL7 was positively correlated with VEGF expression in CRC tissues. CXCL7 was an independent predictor of poor OS of CRC patients (HR = 2.216, 95% CI: 1.069-4.593, P = 0.032), and co-expression of CXCL7 and VEGF of predicted poor OS of 56.96 months. Conclusion: Expression of CXCL7 correlated with VEGF and was associated with poor clinical outcomes in CRC patients.